Effectiveness of Corticosteroid Injections for Treatment of de Quervain's Tenosynovitis. (July 2017) - Oh, Jinhee K.; Messing, Susan; Hyrien, Ollivier; Hammert, Warren C.
Background: Although surgery can provide definitive treatment for de Quervain's tenosynovitis, nonoperative treatment could be preferable if symptoms are predictably relieved. We sought to determine the effectiveness of corticosteroid injections as treatment for de Quervain's tenosynovitis and to evaluate patient characteristics as predictors of treatment outcome.Methods: A retrospective study was conducted using our institutional database International Classification of Disease, version 9 (ICD-9) code list for de Quervain's tenosynovitis. Treatment success was defined as relief of symptoms after 1 or 2 injections. Relief was defined as resolution or improvement to the extent that the patient did not seek further intervention. Failure was defined as a subsequent surgical release or a third injection. Logistic regression analyses were performed to look for univariate associations between patient demographics/comorbidities and risk of treatment failure.Results: The treatment outcome of 222 limbs from 199 patients was studied. Of the 222 limbs, 73.4% (95% confidence interval [CI], 66.9%-79.1%) experienced treatment success within 2 injections, and 51.8% (95% CI, 45.0%-58.6%) experienced success after 1 injection. Body mass index (BMI) >30 and female sex were found to be significantly associated with treatment failure, with a 2.4-fold increase (95% CI, 1.02%-5.72%) in odds and 3.23 times greater (95% CI, 1.08%-9.67%) odds of failure, respectively. Although not reaching statistical significance, African American race, hypothyroidism, and carpal tunnel syndrome suggested increased odds of failure.Conclusions: This study indicates that corticosteroid injections are a useful treatment for de Quervain's tenosynovitis, leading to treatment success 73.4% of the time within 2 injections. This study also suggests that female sex and BMI >30 are associated with increased treatment failure.